CHANGING TRENDS IN THE DIAGNOSIS AND TREATMENT OF LIVER HYDATIDOSIS OVER A 60-YEAR PERIOD: EXPERIENCE OF A TERTIARY REFERRAL CENTER IN AN EUROPEAN ENDEMIC REGION - Stojanovic, Marko (Acta medicae Medianae, 2026)
Serbia is a well-known endemic region for hydatid liver (LH) disease. Although surgery remains the primary treatment modality, significant changes have occurred in the diagnosis and treatment of this disease in recent years. The aim of this study was to retrospectively analyze the demographic and clinical characteristics of patients who had undergone surgical treatment for LH at a tertiary referral center over the past 60 years. The authors conducted a comparative analysis across three 20-year periods: period I (1960–1980), period II (1980–2000), and period III (2000–2020). The ratio of surgeries performed due to LH in the last period (1.23‰) was significantly lower than in the first two periods (5.15‰ and 4.86‰, respectively). A higher incidence in females (1:2.2), cyst localization, and rate of complications have remained consistent over time. The latest standard diagnostic procedures include Ultrasonography (US), Computed tomography (CT), Enzyme-linked immunosorbent assay (ELISA) and Indirect hemagglutination assay (IHA) test. While the management of LH shifts towards less invasive procedures, open surgery remains the gold standard. The tissue-sparing operations were performed in most cases (61.91%). However, there has been a slight increase in the radical surgeries, rising from 25.4% in the first period to 43.15% in the second and 46% in the third period. The surgical approach by Papadimitriou—partial cystopericystectomy plus omentoplasty (PCPCO)—may be the preferred method as it balances the need for radical treatment with tissue preservation in LH surgery. Minimally invasive techniques such as punation aspiration irrigation and respiration (PAIR) and laparoscopy have gradually been introduced over the last two periods, in a small number of carefully selected cases (increasing from 3.4% to 8.1%, respectively).
Keywords: echinococcosis, hydatid disease, liver, diagnosis, therapy